PHASE TRANSFORMATIONS IN STEEL DURING RAPID HEAT TREATMENT - PROHÁSZKA, J. (Periodica Polytechnica Mechanical Engineering, 1988)
Phase transformations in low-carbon steels during rapid heat treatment proceed very differently than under equilibrium conditions. The differences can successfully be utilized for improving the properties of the steels.